Pengaruh Pembiasaan Shalat Dhuha Berjama’ah terhadap Kedisiplinan Belajar Siswa Kelas VIII di MTs Al-Ahsan Kota Bogor - Novita Rahmalia; Zahid Mubarak; Asep Gunawan (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The world of education has many goals to be achieved, one of which is to foster disciplined behavior in students. With the habit of praying dhuha at school, students should be able to understand and develop disciplined behavior in each of them. This study aims to determine the level of habituation of the Dhuha prayer in congregation for class VIII students at MTs Al-Ahsan Bogor City, to determine the level of discipline in class VIII students at MTs Al-Ahsan Bogor City and to analyze the influence of the habituation of Dhuha prayer in congregation on the learning discipline of class VIII students at MTs Al-Ahsan Bogor City. The research method used in this research is quantitative research. This study used a population of all VIII grade students at MTs Al-Ahsan with a total sample of 114 people taken at random. The instruments used in this research are questionnaires and documentation. The data analysis technique in this study used simple linear regression analysis with the help of the SPSS 26 application. The results showed that: First, the habit of praying dhuha in congregation for class VIII students at MTs Al-Ahsan obtained a score in the "good" category with an average value (mean) of 46.94. Second, the learning discipline of class VIII students at MTs Al-Ahsan obtained a score in the "very good" category with an average score (mean) of 46.91. And third, the results of the simple regression test obtained a calculated t value of 14.909 > t table of 1.661, a Sig value of 0.000 <0.05 and a coefficient of determination of 0.665 so that Ho is rejected and Ha is accepted, which means that there is a significant influence between the habit of praying dhuha in congregation on the learning discipline of class VIII students at MTs Al-Ahsan Bogor is 66.5% while the remaining 33.5% is influenced by other factors.